1996
DOI: 10.1097/00000658-199604000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Fasted and Fed Gastrointestinal Motility After Open Versus Laparoscopic Cholecystectomy in Dogs

Abstract: ObjectiveThe authors investigate the recovery of gastrointestinal motility in the fed and fasted state after laparoscopic and open cholecystectomy. Summary Background DataClinical recovery after laparoscopic cholecystectomy is known to be more rapid than after conventional open cholecystectomy. However, the actual effect of a laparoscopic approach on gastrointestinal motility, particularly fed-state motility, is not well investigated. MethodsLaparoscopic (LAP, n = 6) or open (OPEN, n = 6) cholecystectomy was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 24 publications
1
19
0
1
Order By: Relevance
“…There have been few reports describing the relationship between the recovery of fasted and fed-state gastric motility after surgery. Only two previous articles by Hotokezaka et al 15,16 showed that the presence of gastric myoelectric dysrhythmias during fasting did not accurately predict fed-state gastric emptying after abdominal surgery in dogs. This is the first study to analyze factors affecting the recovery course of gastric phase 3 after PPPD and to elucidate whether early recovery of gastric phase 3 would reflect the early improvement of the fed-state gastric emptying function to the normal level in patients after PPPD.…”
Section: Discussionmentioning
confidence: 96%
“…There have been few reports describing the relationship between the recovery of fasted and fed-state gastric motility after surgery. Only two previous articles by Hotokezaka et al 15,16 showed that the presence of gastric myoelectric dysrhythmias during fasting did not accurately predict fed-state gastric emptying after abdominal surgery in dogs. This is the first study to analyze factors affecting the recovery course of gastric phase 3 after PPPD and to elucidate whether early recovery of gastric phase 3 would reflect the early improvement of the fed-state gastric emptying function to the normal level in patients after PPPD.…”
Section: Discussionmentioning
confidence: 96%
“…One study by Hotokezaka et al showed that GI motility, in general, was less affected, following laparoscopic vs. open cholecystectomy in dogs, only in the fed state, while colonic transit time was not affected by either procedure [16]. In another study of 46 patients, undergoing laparoscopic or conventional cholecystectomy, Geng et al showed that the laparoscopic group had significantly shorter anorectum exhaust time and peristaltic sound recovery time [8].…”
Section: Discussionmentioning
confidence: 99%
“…When compared to open procedures, laparoscopic surgical techniques were accompanied more rarely by inflammatory responses [18]. Applying these techniques, gastric emptying and fasted state of gastrointestinal motility were improved and the rate of POI was reduced [19]. The use of opioid-free or opioid-reduced analgesic regimens such as nonsteroidal anti-inflammatory drugs or other agents have been demonstrated to reduce POI [3].…”
Section: Discussionmentioning
confidence: 99%